EFL Students' Perceptıon of Gamıfıcatıon-Integrated Englısh Language Educatıon - Orak, Suheyla Demirkol (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2025)
Over the decades, English language education has been reshaped in the same line with the technological advancements, and the target audience's interest areas. In the 21st century, students' motivation and extramural learning have had a significant impact on language education since they both encourage subconscious learning. At that moment, game-based learning activities take the lion's share since the enjoyment factor in learning situations is the center of attention for the students. However, there is a gap in the literature addressing the investigation of EFL students' perception of placing the games as a teaching tool. In the current quantitative research study, EFL students' perception of gamification-integrated English language education was investigated by adopting a comparative approach in terms of several variables: age, gender, department, and grade. 394 students took part in the actual study after piloting, and a descriptive comparative research design was adopted. Apart from preliminary statistical checks (multicollinearity, linearity, residual statistics, distribution of normality, outlier analysis), Independent samples t-test and one-way ANOVA were conducted. Findings have shown that students hold a lukewarm to positive perception of gamification-integrated English language education regarding perceived engagement, motivation, classroom atmosphere, and comprehension. However, while students' age, department, and grade differ significantly in comparison to their perception, their gender has not yielded any differences. Findings imply that gamification-integrated English language education can be adopted as an approach, and can be benefitted in class, or as extramural, and extracurricular activity types to increase students' engagement and reduce anxiety levels.
Keywords: Comprehension; extramural activity; gamification; game-based education; motivation.